Library Promotion Strategy in the Digital Era: Study at Malang City Public Library - Milenia, Nurbeta Dela; Riady, Yasir; Prasakti, Angga Warda (LADU: Journal of Languages and Education, 2024)
Background: The library is an institution that has an essential role in society. The efforts made by the library to carry out this role ensure that the public knows about the library's existence. The public can only use the library if they know its role. Thus, so that libraries can continue to carry out their role, libraries need to develop library promotion strategies. Promotion as a marketing activity carried out by libraries is essential so that the public knows about the products that the library can use. Society also uses digital technology to meet information needs in the digital era. However, society's tendency to use digital technology does not reduce the role of libraries as information institutions to meet society's information needs. The development of digital technology can be utilized to increase the existence of libraries through library promotion strategies. Purpose: This article reviews various promotional strategies libraries can implement using digital technology. Design and methods: The research method used is qualitative, with data collection techniques through document study and library observation via websites. Results: Promotional strategies that libraries can carry out are publications, advertising, sales promotions, personal sales, and digital marketing. Obstacles encountered in carrying out promotional activities are a consideration for libraries in determining promotional strategies that are appropriate to the conditions of the library.